Optimization of biopolymer production in shake flask using oil palm trunk sap medium - Mazia, Awang (2010)
Polyhydroxybutyrate (PHB) is a biodegrable polymer which is an intracellular product produce by a bacteria. This research is conducted to optimize the biopolymer production in shake flask using oil palm trunk sap medium with Cupriavidus necator. It consists of four major phases starting with the innoculum development process, followed by the fermentation process, the analysis of the process and the process optimization. The innoculum development process is done to produce the 50 ml of innoculum Cupriavidus necator in shake flask by using growth media and incubated in incubator shaker with set point values for agitation speed and temperature. This experiment is followed with the fermentation process involving the manipulation of the parameters agitation speed, temperature and percent volume of oil palm trunk sap. Among the experimental points, it is found that the highest yield of PHB is produced in conditions of 150 RPM agitation speed, 32oC temperature and 20% volume of oil palm trunk sap. This experiment was followed by mathematical analysis using Yates’ Method to study the main effects and interactive effects of changing the level of experimental variables. The calculation showed that percent volume of oil palm trunk sap has a significant main effect on PHB production while the significant interactive effect is the combination of agitation speed and percent volume of oil palm trunk sap. From the experiment for Method of the Path of Steepest Ascent the highest production of PHB occurred at parameter 31.1 oC for temperature, 138 RPM for agitation speed and 33.8% for percent volume of oil palm trunk sap